2019
DOI: 10.1523/jneurosci.0708-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Counteracts the Psychotropic Side-Effects of Δ-9-Tetrahydrocannabinol in the Ventral Hippocampus through Bidirectional Control of ERK1–2 Phosphorylation

Abstract: Evidence suggests that the phytocannabinoids ⌬-9-tetrahydrocannabinol (THC) and cannabidiol (CBD) differentially regulate salience attribution and psychiatric risk. The ventral hippocampus (vHipp) relays emotional salience via control of dopamine (DA) neuronal activity states, which are dysregulated in psychosis and schizophrenia. Using in vivo electrophysiology in male Sprague Dawley rats, we demonstrate that intra-vHipp THC strongly increases ventral tegmental area (VTA) DA neuronal frequency and bursting ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 78 publications
4
40
0
2
Order By: Relevance
“…The molecular mechanisms underlying CBD's apparent mitigation of some pharmacological effects of THC are poorly understood (Boggs et al, 2018) and still have to be fully investigated, keeping in mind that the pharmacological targets for CBD are numerous and not fully established, some being controversial. Furthermore, the mechanisms by which THC and CBD exert their effects are different and are more complicated when delivered in combination (Russo, 2011), rendering the attribution of the actions of the THC + CBD combination to one proposed molecular mechanism more difficult (Hudson et al, 2019;Bassir Nia and Hurd, 2018). Whichever of the diverse mechanisms is involved, it seems imperative that CBD should be integrated in any cannabis preparation and its ratio to THC should be taken into account, due to the multiple beneficial effects of CBD in moderating or completely inhibiting THC effects, as we showed here.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying CBD's apparent mitigation of some pharmacological effects of THC are poorly understood (Boggs et al, 2018) and still have to be fully investigated, keeping in mind that the pharmacological targets for CBD are numerous and not fully established, some being controversial. Furthermore, the mechanisms by which THC and CBD exert their effects are different and are more complicated when delivered in combination (Russo, 2011), rendering the attribution of the actions of the THC + CBD combination to one proposed molecular mechanism more difficult (Hudson et al, 2019;Bassir Nia and Hurd, 2018). Whichever of the diverse mechanisms is involved, it seems imperative that CBD should be integrated in any cannabis preparation and its ratio to THC should be taken into account, due to the multiple beneficial effects of CBD in moderating or completely inhibiting THC effects, as we showed here.…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical consideration given that the Δ9–THC:CBD ratios and concentrations can vary dramatically in available recreational cannabis products. In addition, CBD has been shown in clinical and preclinical studies to block or strongly mitigate the neuropsychiatric side-effects of Δ9–THC ( 45 47 ), meaning that high Δ9–THC/low CBD cannabis products may pose additional risks during prenatal development. Thus, while the preponderance of recent evidence suggests that prenatal cannabis use adversely impacts neonatal outcomes, a scientific consensus requires careful consideration of relevant variables such as polydrug use, the frequency and timing of prenatal cannabis use, and the relative chemical composition of the cannabis being consumed.…”
Section: Physiological Outcomes Of Prenatal Cannabinoid Exposurementioning
confidence: 99%
“…It is important to point out that the modulatory effects CBD exerts over the psychotomimetic actions of THC in the central nervous system 10 might come from its negative allosteric modulation of CB 1 receptors, as reported by Laprairie et al 21 To further reinforce this molecular relation between THC and CBD, Hudson et al 24 showed that CBD reverses THC associated side‐effects due to inhibition of THC‐mediated ERK phosphorylation in the ventral hippocampus (vHipp) of Sprague Dawley rats, as assessed by the western blot technique. Furthermore, using the open field test, the authors observed differential effects of THC vs CBD on anxiety‐like behaviours.…”
Section: Cannabinoid Systemmentioning
confidence: 94%